2016
DOI: 10.5937/geopan1603168m
|View full text |Cite
|
Sign up to set email alerts
|

Environment of estates and crime prevention through urban environment formation and modification

Abstract: Due to the significant impact of criminality on the quality of life in a particular territory, criminality is attracting more and more attention from local authorities which are trying to reduce it. In this respect, the concept of CPTED (Crime Prevention Through Environmental Design) which is quite often used outside of Slovakia and is based on prevention of criminality through the appropriate design of urban environments, seems to be useful. The study offers the characteristics of CPTED principles and also su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The existing works on individual aspects of the study of spatial factors in the security mechanism are isolated works by specialists in various fields of knowledge (sociology, urban planning, information technology, criminal law). At the same time, CPTED's strategy of focusing on finding security vulnerabilities through natural access control, natural surveillance, area strengthening, public space maintenance and community prevention has proven to be useful and effective as a very concrete strategy for preventing crime and changing individual perceptions of territory from a security/unsecurity perspective, integrated into an interdisciplinary approach of "geo-warning" [5], since "the proper design and effective use of an artificial environment can lead to a reduction in crime and fear of crime, as well as to an improvement in the quality of life" [7], which suggests the need to continue to develop it in the light of experience with its application.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The existing works on individual aspects of the study of spatial factors in the security mechanism are isolated works by specialists in various fields of knowledge (sociology, urban planning, information technology, criminal law). At the same time, CPTED's strategy of focusing on finding security vulnerabilities through natural access control, natural surveillance, area strengthening, public space maintenance and community prevention has proven to be useful and effective as a very concrete strategy for preventing crime and changing individual perceptions of territory from a security/unsecurity perspective, integrated into an interdisciplinary approach of "geo-warning" [5], since "the proper design and effective use of an artificial environment can lead to a reduction in crime and fear of crime, as well as to an improvement in the quality of life" [7], which suggests the need to continue to develop it in the light of experience with its application.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…An open park space will meet the diversified needs of urban people, so it is necessary to effectively improve the connectivity of the park area space and effectively link the multi-dimensional characteristics of renovated industrial parks. An important factor regarding the user per-ception of industrial heritage parks is safety, and the parks that contain gazetted attributes can be renovated and subsequently renewed to enhance environmental safety by taking into account certain rules based on crime prevention, which can be realized through the introduction of the CPTED (Crime Prevention Through Environmental Design) concept [41] into the design. The CPTED concept is the proper design and effective use of a built environment, which can lead to a reduction in the incidence of crime and fear of crime as well as to improvement in the quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Perez-Tejera, Anguera, Guardia-Olmos, Dalmau-Bueno, and Valera [73] and Sun, Lin, and Yin [54] found that women felt safer when living in a neighborhood for a long time, even though it did not have additional security solutions. Matlovičová, Mocák, and Kolesárová [76] analyzed environmental planning solutions that could increase security-such as the creation of monitored spaces (increases the feeling of security), the use of greenery near buildings (to protect against vandalism), and the installation of lighting (ensures the ability to notice other people). When choosing revitalization solutions, it is important to consider the safety of the most vulnerable groups of people, because designers have the potential to prevent crime from happening [77].…”
Section: Literature Reviewmentioning
confidence: 99%